PERLINDUNGAN TERHADAP PASAR TRADISIONAL DI TENGAH EKSPANSI PASAR RITEL MODERN - Noor, Afif (Economica: Jurnal Ekonomi Islam, 2013)
Modern retail market, especially in Central Java experiencing tremendous growth lately, based on the data, in 2004 the number reached 1,496 traditional markets, while the modern market amounted to 232. Different conditions occurred in 2008, the number of traditional market just reached 1,443 while the modern market reached 399. That means there is a negative growth in traditional markets. In 2010 the modern retail market growth reached 10.2% (1,852 outlets). This condition is one side has a positive effect because it means showing the high investment in the real sector, but on the other result in the more traditional markets entrapment, especially the modern retail market using the franchise system to begin operations 24 hours per day. Therefore, the protection of traditional markets as the center of economic activities of small and medium-sized enterprises should be done to ensure the sustainability of small and medium enterprises.